Synthesis of Triazole derivative: [4-(benzylideneamino)-5-phenyl -4H-1,2,4 – triazole-3-thiol] - Singh, Ashok Kumar; Kandel, Khem Raj (Journal of Nepal Chemical Society, 2013)
The basic nucleus 4-(amino)-5-phenyl-l-4H-1,2,4-triazole-3-thiol has been synthesized by cyclisation of potassium dithiocarbazinate with hydrazine hydrate using water as solvent under reflux condition for 3-4 h. The compound which has been synthesized successfully was subjected to condensation with benzaldehyde to synthesize 4-(benzylideneamino)-5-phenyl -4H-1,2,4 – triazole-3-thiol (Schiff base). The compounds were confirmed by physical parameters (melting point), chromatographic methods (TLC) and spectroscopic methods (IR and NMR).DOI: http://dx.doi.org/10.3126/jncs.v30i0.9391Journal of Nepal Chemical Society Vol. 30, 2012 Page:  174-177 Uploaded date: 12/20/2013